Automated Energy Saving Technology for Providing of Stability - Nurillaevich, Babaev Nasrulla; Sagidullaevna, Tadjibaeva Guljakhan (European Journal of Life Safety and Stability (2660-9630), 2022)
Fuel and energy resources of our planet are not unlimited, the increase in the consumption of fuel and energy resources is associated with the growth of the Earth's population. This article presents general directions, offers energy saving technologies with the use of IT. Buildings consume a significant amount of energy to maintain comfortable living conditions for residents, which implies heating the premises and preparing hot water, ventilation and air conditioning / cooling, as well as electricity supply for the needs of lighting and other household appliances. There are advanced technical solutions for buildings that reduce energy consumption, carbon dioxide emissions and energy losses, while ensuring maximum thermal comfort and safety for occupants. In general, such technologies either reduce energy consumption or increase the efficiency of its use